2009
DOI: 10.1103/physrevlett.103.100401
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Angular Momentum and Geometric Spin Hall Effect of Light

Abstract: We present a novel fundamental phenomenon occurring when a polarized beam of light is observed from a reference frame tilted with respect to the direction of propagation of the beam. This effect has a purely geometric nature and amounts to a polarization-dependent shift or split of the beam intensity distribution evaluated as the time-averaged flux of the Poynting vector across the plane of observation. We demonstrate that such a shift is unavoidable whenever the beam possesses a nonzero transverse angular mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
231
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 246 publications
(238 citation statements)
references
References 25 publications
6
231
0
1
Order By: Relevance
“…Then, we have calculated the commutation relations between the Cartesian components ofĴ ,L,Ŝ and we have found that they differ from the standard one. In particular, whileL z is still a bona fide generator of rotations around the propagation axis z, the transverse componentsL x andL y commute and, as it was already found at a classical level [12], they are strictly connected with the transverse coordinates y and −x of center of the beam, respectively. Finally, as a realistic example illustrating the above mentioned connection, we calculated the expectation value ofĴ between multi-mode coherent states of the electromagnetic field.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Then, we have calculated the commutation relations between the Cartesian components ofĴ ,L,Ŝ and we have found that they differ from the standard one. In particular, whileL z is still a bona fide generator of rotations around the propagation axis z, the transverse componentsL x andL y commute and, as it was already found at a classical level [12], they are strictly connected with the transverse coordinates y and −x of center of the beam, respectively. Finally, as a realistic example illustrating the above mentioned connection, we calculated the expectation value ofĴ between multi-mode coherent states of the electromagnetic field.…”
Section: Discussionmentioning
confidence: 98%
“…In physical terms, the essence is that any well collimated beam is basically an eigenstate of the zcomponent of the linear momentum operator which, for such beams, practically reduces to a c-number. Thus, in order to recover canonical commutation relations, it is necessary to deal with beams with either high angular aperture θ 0 for whose our first-order approximation breaks down, or with a direction of propagation that deviates from the reference axis z by an angle grater than θ 0 [12]. As a final remark, it should be noticed that violations of canonical commutation relations for the angular momentum of an electromagnetic field of arbitrary shape, were already reported by van Enk and Nienhuis [10].…”
Section: A Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the limit of tight focusing of light beams, the electromagnetic field distribution can become highly complex in the focal plane [5][6][7][8]29]. In this context, the occurrence of longitudinally oscillating field components or, more generally, of three-dimensional field distributions gives rise to a variety of interesting effects and phenomena, including spin-to-orbit coupling [30], transverse angular momentum [31][32][33][34], the creation of complex polarization topologies [35] at the nanoscale, and also the possibility of focusing light more tightly, as observed for instance for radially polarized light [4,7].…”
mentioning
confidence: 99%